2011
DOI: 10.1097/wno.0b013e3181e7e4c8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroretinitis With Retrobulbar Involvement

Abstract: Two patients with neuroretinitis are presented, both having MRI abnormalities of the orbital portion of the optic nerve. We review previous reports of CT and MRI findings in patients with neuroretinitis and propose a spectrum of neuroimaging abnormalities in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…We evaluated an immunosuppressed patient who developed bilateral EBV neuroretinitis, with subacute swelling of the optic discs, accumulation of intraretinal and subretinal fluid originating from the disc leakage, and finally precipitation of lipid within the neurosensory retina once the fluid resorbed several weeks later (9). The thickening and enhancement of the left retrobulbar optic nerve seen on MRI here has been previously reported in the setting of neuroretinitis (10, 11). The absence of right optic nerve enhancement on repeat MRI could be explained by the course of high-dose steroids that the patient had just received, or a more localized involvement of the optic nerve head on the right compared to the left side.…”
Section: Discussionsupporting
confidence: 77%
“…We evaluated an immunosuppressed patient who developed bilateral EBV neuroretinitis, with subacute swelling of the optic discs, accumulation of intraretinal and subretinal fluid originating from the disc leakage, and finally precipitation of lipid within the neurosensory retina once the fluid resorbed several weeks later (9). The thickening and enhancement of the left retrobulbar optic nerve seen on MRI here has been previously reported in the setting of neuroretinitis (10, 11). The absence of right optic nerve enhancement on repeat MRI could be explained by the course of high-dose steroids that the patient had just received, or a more localized involvement of the optic nerve head on the right compared to the left side.…”
Section: Discussionsupporting
confidence: 77%
“…The consistent absence of these changes and the failure to develop clinical MS on long-term follow-up (87) have put this issue to rest. Two additional cases with similar findings have been reported (46,102). Schmalfuss et al (101) evaluated the MRI findings in 82 patients with various optic neuropathies, including 9 with CSD.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 88%
“…Schmalfuss et al (101) evaluated the MRI findings in 82 patients with various optic neuropathies, including 9 with CSD. A combination of optic nerve and sheath enhancement was seen on CT in 1 case of idiopathic NR (104) and on MRI in 1 patient with recurrent idiopathic NR (46). The authors suggested that this ''short segment enhancement'' is highly specific for CSD-NR.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 98%
See 1 more Smart Citation
“…Fat suppression of the orbital soft tissue further supported the diagnosis of optic perineuritis. Vaphiades et al 8 reported two patients with neuroretinitis in which a contrast enhanced fat-suppressed orbital MRI revealed diffuse enhancement of the optic nerve and sheath on both patients.…”
Section: Discussionmentioning
confidence: 99%